Synthesis, structure and biological activity of three platinum (II) complexes bearing alkyleugenoxyacetate (alkyl: ethyl or propyl) and heterocyclic amine - Thanh Chi, Nguyen Thi; Da, Tran Thi (Vietnam Journal of Chemistry, 2014)
Three organometallic complexes of platinum(II), [PtCl2(Eteug)(C9H7N)] (P1), [PtCl(Eteug)(C9H6NO)] (P2) and [PtCl(Preug)(C9H6NO)] (P3), have been synthesized for the first time. The structures of P1, P2 and P3 were determined by platinum analysis, EDX, IR, 1H NMR, 13C NMR and NOESY NMR spectra. In these complexes, the allyl group of ethyl eugenoxyacetate (Eteug) and propyl eugenoxyacetate (Preug) coordinate with platinum(II) in an η2 manner, quinoline (C9H7N) coordinates with Pt(II) via N atom, deprotonated 8-hydroxyquinoline (C9H7NO) coordinates with Pt(II) via N and O atoms. In all the complexes, the N atom occupies the trans-position in comparison to the allyl group. All P1, P2 and P3 exhibit a potent cytotoxicity on Hep-G2 human cancer cell line with small IC50 values of 6.97, 0.31 and 1.27 μg/ml, respectively. Keywords: Alkyleugenoxyacetate, platinum(II) complexes, heterocyclic amine, cytotoxicity.